Elaboración de un módulo didáctico mediante el diseño editorial e ilustración para promover el interés en el aprendizaje del idioma kichwa en los estudiantes del 9° ciclo de educación básica de la unidad educativa Jatari Unancha del cantón Latacunga, provincia de Cotopaxi, en el año 2016 - Changoluisa Martínez, Leonardo Wladimir (2016)
Improving the education quality and the student learning at educational institutions is an issue that must be paying attention in order to raise the students interest and understanding in their classroom. Often this problem lies in the educational materials used by teaching a subject, because they do not have an optimum graphic quality in order to make easier both teaching teachers and students learning. Thus this research has a very important issue in the education because of not only the existing educational material will be improved, making it more didactic and entertaining for students, besides being focused on the Kichwa subject, it is making a worthy contribution in order to value the mother tongue which is a fundamental part of our cultural identity in the Ecuadorian highlands and is decreasing over time….